2018
DOI: 10.1523/jneurosci.2484-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Negative Regulation Between Lmx1a and Lmo4 Is Required for Inner Ear Formation

Abstract: LIM-domain containing transcription factors (LIM-TFs) are conserved factors important for embryogenesis. The specificity of these factors in transcriptional regulation is conferred by the complexes that they form with other proteins such as LIM-domain-binding (Ldb) proteins and LIM-domain only (LMO) proteins. Unlike LIM-TFs, these proteins do not bind DNA directly. LMO proteins are negative regulators of LIM-TFs and function by competing with LIM-TFs for binding to Ldb's. Although the LIM-TF Lmx1a is expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…By removing one allele of Bmp2 in the Ntn1 knockouts, it reduces the inhibitory effect of the canal rim on the resorption domain and alleviates the non-resorption phenotype in Ntn1 knockouts (Figs 7 and 10A, Table 2). Such reciprocal inhibition has been described for Lmx1a and Lmo4 recently (Huang et al, 2018). Although Lmx1a and Lmo4 regulate each other in forming transcriptional complexes, the mechanisms underlying the reciprocal inhibition between Bmp2 and Ntn1 will require further investigation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…By removing one allele of Bmp2 in the Ntn1 knockouts, it reduces the inhibitory effect of the canal rim on the resorption domain and alleviates the non-resorption phenotype in Ntn1 knockouts (Figs 7 and 10A, Table 2). Such reciprocal inhibition has been described for Lmx1a and Lmo4 recently (Huang et al, 2018). Although Lmx1a and Lmo4 regulate each other in forming transcriptional complexes, the mechanisms underlying the reciprocal inhibition between Bmp2 and Ntn1 will require further investigation.…”
Section: Discussionsupporting
confidence: 57%
“…Reciprocal inhibition between the rim and resorption domain of the canal pouch during canal formation have been well documented (Abraira et al, 2008; Huang et al, 2018). Our results indicate that broad expression of Bmp2 in the canal pouch (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lmx1a has been suggested to be part of the transcription factor network, together with Gata3, that define SGN from the VGN population in early development stages (Appler and Goodrich, 2011). Besides, loss of Lmx1a also leads to an expansion of the vestibular ganglion region of the inner ear (Huang et al, 2018). Despite these reports, which establish the importance of Lmx1a in the inner ear, little attention has been paid to the expression of Lmx1a in the SGN population.…”
Section: Discussionmentioning
confidence: 99%
“…All prosensory domains of the otocyst express the SRY-box transcription factor Sox2 and the Notch ligand Jag1. The LIM homeobox transcription factor Lmx1a is expressed in the non-sensory regions of the otocyst, and mutation of this gene causes a failure of many of the prosensory patches to correctly separate and individuate [27,38,39]. The vestibular prosensory domains can then be further distinguished by the expression of genes specifically expressed in the future cristae and maculae.…”
Section: Notch-mediated Lateral Induction Plays a Key Maintenance Rolmentioning
confidence: 99%
“…An interesting feature of the canonical prosensory markers, Sox2 and Jag1, and the canonical non-sensory marker Lmx1a, is that they are all expressed in a broad pattern throughout the otic cup as it closes [17,26,43]. However, as prosensory development begins, the expression of all three genes shifts and eventually separates over a 48 h period until Sox2 and Jag1 demarcate prosensory domains and Lmx1a is relegated to non-sensory epithelium [38,[44][45][46][47][48][49]. Fate mapping of Sox2 expression using a Sox2CreERT2 knock-in mouse has confirmed that the broad domain of Sox2 expressing cells present in in the early otic cup will form both future sensory and non-sensory tissues [50,51].…”
Section: Notch-mediated Lateral Induction Plays a Key Maintenance Rolmentioning
confidence: 99%